Pendampingan Pembelajaran Bahasa Inggris Berbasis Aplikasi BDL Pada Mahasiswa Kardiovaskuler Universitas Megarezky - Hasnani; Hesti Oktaviana (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
English language skills are one of the urgent needs for cardiovascular students at Megarezky University. Because the cardiovascular field is concerned with heart health, it often involves interaction with researchers, health practitioners, and international colleagues. The main purpose of application-based English learning assistance for cardiovascular students is to improve English language skills through the use of interactive learning applications. This community service uses a descriptive method. Based on the results of feedback and evaluation of this training activity, the PKM Team concluded that BDL application-based English learning assistance activities can improve student communication skills. Where Cardiovascular students become more able to communicate fluently and effectively in English. They can participate in group discussions, deliver presentations, and write reports well in English. This ability is invaluable in the world of work, especially in the cardiovascular field which involves interaction with researchers, health practitioners, and international colleagues.